Inovasi Penilaian Pembelajaran Pelatihan Penilaian Diagnosis, Otentik, dan Akhir Unit Terdiferensiasi - Rosfiani, Okta; Hermawan, Cecep Maman; Abdullah, Syamsudin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The educators' inadequate grasp of conducting thorough and meaningful assessments has harmed the quality of learning in partner schools. The goal of this community service program is to enhance the competency of educators by offering instruction in differentiated assessments that are authentic, diagnostic, and end-of-unit. Three main techniques for implementation are on-going mentoring, hands-on training, and theoretical instruction. The program's outcomes show that teachers' abilities to create and administer tests that are more pertinent to students' needs and flexible have significantly increased. The program's results include assessment modules, educator-produced assessment products, and an increase in positive student responses to learning. These findings are critical for promoting higher-quality education and more productive learning in affiliated schools.